Classroom Management Experiences Through the Lens of Non-Education Graduate Mathematics Instructors - Pantaleon, Alfred; Rodriguez, Mary Joy; Villanueva, ZJ; Visaya, Avelina (Journal of Interdisciplinary Perspectives, 2025)
This phenomenological research focuses on the classroom management of non-education graduate mathematics instructors in Ilocos Sur Polytechnic State College (ISPSC). The work applied transcendental phenomenological research design and purposive sampling to choose five participants with teaching experience in classroom management ranging from one to three years. Semi-structured interviews were used to elicit in-depth perspectives, and thematic analysis indicated three main themes. The three areas of significance include (1) the area of classroom management difficulties, (2) the area of classroom management approaches, and (3) the area of professional development. The study reveals the challenges educators face in their classrooms concerning the micro level of interactions, including how to address diverse student behaviors emerging from sociocultural and technological contexts. In addition, the emphasis is placed on the participants’ approaches to addressing these problems and their constant demand for relevant professional learning to enhance classroom management expertise. This study enhanced our appreciation of the difficulties of teacher learning in higher education, especially those with no educational background. It points out that much attention should be given to offering them the requisite equipment and training to preserve the joyful learning atmosphere.